Peningkatan Hasil Belajar Siswa Tema 4 dengan Menggunakan Metode Kooperatif Tipe Example Non Example Kelas 2 SD Negeri Sokokidul - Janah, Asna Fatkhul; Istiqomah, Nalimatul; Novita, Erma; Hanik, Elya Umi (Lembaga Yasin AlSys, 2021)
This research is motivated by several problems that occur in the learning activities of SD Negeri SokoKidul, so that the learning outcomes obtained by students have not reached the predetermined KKM. Based on observations, it is known that there are still students who are passive in participating in the learning process and the lack of variety of teachers in using methods affects the low learning outcomes of students. The purpose of this study was to determine the increase in student learning outcomes of grade 2 students of SD Negeri SokoKidul in learning theme 4 sub-theme 2 by using a cooperative method of example non example. This research is included in the Classroom Action Research (CAR) which was carried out in two cycles. Each cycle consists of one meeting. One cycle consists of 4 stages of activity, namely the planning stage, the implementation stage, the observation stage and the reflection stage. The subject of this research is grade 2 SD Negeri SokoKidul with a total of 16 students consisting of 8 male students and 8 female students, in learning theme 4 sub-theme 2 for the 2020/2021 academic year using the 2013 curriculum. Data collection techniques used in this study are qualitative and quantitative data analysis. For the learning outcomes of students who achieve KKM in learning theme 4 sub-theme 2. The indicator of success in this study is an increase in student learning outcomes marked by the achievement of minimum completeness criteria (KKM) in learning theme 4 sub-theme 2.